Laparoscopic Surgery for Rectal Cancer - Viola, Marcelo; Solla, Gonzalo (Cirugía del Uruguay, 2025)
Co-authors: Marcelo Laurini, Leticia Turconi, Viviana Braggio, Alejandra Inderkum, Noelia Brito, Alexandra Duffau, Alejandro Soumastre, Fabiana Domínguez, Federico Durán, Noelia Medina, Marcela Umpierrez. Introduction. Rectal cancer is an entity with a great health impact due to its high incidence and mortality. At a global level, according to the records in 2020, they showed an incidence of colorectal cancer in the world of 1.93 million. Being the third most frequent cancer and the second cause of death from cancer, representing almost 900,000 deaths from this disease worldwide. Uruguay does not escape these global figures, according to the CHLCC records, it ranks second in incidence and mortality from cancer in women and third in men. Approximately 2,000 cases of colorectal cancer are detected annually and 1,000 die from this cause. A long way has been traveled in the search to achieve the best results in the treatment of rectal cancer; where this has changed exponentially in the last 30 years. The development of new surgical techniques, the introduction of new therapies and the role of the surgeon, where he becomes one more participant, within a multidisciplinary team and not the "main actor". All of this has contributed to improving the prognosis of colorectal cancer, reducing morbidity and mortality rates, as well as disease-free time and overall survival. In 1991, Jacobs reported the first laparoscopic colectomy, which generated great initial enthusiasm among surgeons, but the difficulties that this entailed quickly became evident. In the first decade of the 2000s, large multicenter prospective studies began to be reported with 10-year oncological results, which demonstrate not only the oncological safety of this approach, but also, in some cases, improved survival and disease-free time. Today, laparoscopic (and robotic) surgery has become a fundamental tool for the surgical treatment of rectal cancer. In this work, we will try to communicate our experience over the last few years in the treatment of rectal cancer, referring to: aspects of perioperative care, diagnosis and the importance of high-resolution nuclear magnetic resonance, relevant points of the anatomy of the rectum and their implications in surgery, anesthetic aspects, the role of the surgeon, and we will discuss how we systematize our surgeries. Objective. To show the experience of a multidisciplinary team in laparoscopic surgery for rectal cancer over more than a decade, sharing different aspects of the procedure. Material and methods. We analyze different aspects of our daily practice in the surgical treatment of rectal cancer, referring to different aspects of the same that we have already discussed. Conclusions. According to the different chapters developed in this work, we demonstrate that it is feasible to perform in our setting, by a multidisciplinary team dedicated and trained in said procedure, involving not only the anesthetic-surgical team, but also imaging, oncology, nutrition, and a nurse who is the link between the entire team and the patient and his family. This should be the center of the entire care process.